Axon diameter determines the mouse optic nerve compound action potential profile in response to varying stimulus frequency - Hopper, Amy J. (2023)
The mouse optic nerve (MON) is a central white matter tract, whose axons range in diameter from 0.2 to 2.7 µm. In the adult animal all the axons are myelinated, conferring increased conduction velocity. Increased conduction velocity can also be achieved by increasing axon diameter. However, current thinking considers that although large axons conduct quickly, this is unlikely to be the primary function of large axons in the MON. The surface area to volume considerations, and the consistent mitochondrial density in the axoplasm, result in larger axons containing an increased number of mitochondria, capable of efficiently dealing with energy perturbations and maintaining ion equilibration.